Harnessing data science to improve integrated management of invasive pest species across Africa: An application to Fall armyworm (Spodoptera frugiperda) (J.E. Smith) (Insecta: Lepidoptera: Noctuidae) - Ritter A. Guimapi; Saliou Niassy; Bester Tawona Mudereri; Elfatih M. Abdel-Rahman; Ghislain T. Tepa-Yotto; Sevgan Subramanian; Samira A. Mohamed; Karl H. Thunes; Emily Kimathi; Komi Mensah Agboka; Manuele Tamò; Jean Claude Rwaburindi; et al. (Elsevier BV, 2023)
Abstract